Corporatization in the Public Sector: Explaining the Growth of Local Government Companies. (22nd April 2019) - Andrews, Rhys; Ferry, Laurence; Skelcher, Chris; Wegorowski, Piotr
Abstract: The creation of companies by local governments to provide public services—referred to as "corporatization"—is an example of systemic public entrepreneurship that is popular across the world. To build knowledge of the antecedents of public sector entrepreneurship, the authors investigate the factors that lead local governments to create companies for public service delivery. Using zero‐inflated negative binomial regressions to analyze secondary data from 150 major English local governments for 2010–16, the authors find that governments with higher levels of grant dependence and debt dependence are more involved in the creation and operation of companies, as are larger governments. Further analysis reveals that very low and very high managerial capabilities are strongly associated with more involvement in profit‐making companies, while local government involvement in companies is more prevalent in deprived areas. At the same time, government ownership of companies is more common in areas with high economic output .